Influence of graduation towers in Inowrocław Spa Park (Poland) on chemical parameters of Mollic Gleysols - Krzyżaniak-Sitarz, Magdalena (Ecological Questions, 2011)
Calcium was the dominant element in the sorption complex of the analysed soils, regardless of the location of a soil profile. Moreover, in most of the endopedons, the concentration of Ca2+ was two or even three times higher than in non-saline soils, which were not affected by anthropopressure. One should, however, emphasize the fact that graduation towers are significant but not the dominant source of calcium in the analysed soil profiles. The concentration of Ca2+ is also strongly affected by the vicinity of the urban area and lime plants, as well as by the composition of the parent rock. The soils of the Spa Park in the town of Inowrocław are Mollic Gleysols with the elevated content of sodium, which together with a small amount of atmospheric precipitation and a constant inflow of sodium from the graduation towers, can bring about negative changes in their physical properties and the composition of the sorption complex. This negative influence of sodium cations can be counterbalanced by a high content of calcium ions. Among water-soluble anions, chloride anions had the highest concentration. The concentration of Cl- in the aqueous soil solution was increasing together with the depth of profiles and was significantly decreasing with the increasing distance from the graduation towers. Moreover, in the profiles located near the graduation towers, the concentration of chlorides in all soil horizons was higher than the permissible limit of 10 mg∙100 g-1.